(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
The most important task of the modern education system is the purposeful formation of a national idea among young people that reflects the historical memory, spiritual and moral values and cultural traditions of the people. In the context of globalization and the rapid development of information technology, the process of educating the younger generation requires the use of innovative pedagogical approaches capable of integrating national values into educational activities. The article discusses the main modern pedagogical capabilities, methods and technologies that make it possible to effectively form a national idea among young people. Digital educational resources, interactive teaching methods, project activities, ethnopedagogical approaches, as well as the potential of family-community interaction are analyzed. Special attention is paid to the issues of harmonization of traditional and modern pedagogical tools to ensure the integr.